Impaired TCA cycle flux in mitochondria in skeletal muscle from type 2 diabetic subjects: Marker or maker of the diabetic phenotype? - Gaster, Michael; Nehlin, Jan O.; Minet, Ariane D. (Archives of physiology and biochemistry, 2012)
The diabetic phenotype is complex, requiring elucidation of key initiating defects. Recent research has shown that diabetic myotubes express a primary reduced tricarboxylic acid (TCA) cycle flux. A reduced TCA cycle flux has also been shown both in insulin resistant offspring of T2D patients and exercising T2D patients in vivo. This review will discuss the latest advances in the understanding of the molecular mechanisms regulating the TCA cycle with focus on possible underlying mechanism which could explain the impaired TCA flux in insulin resistant human skeletal muscle in type 2 diabetes. A reduced TCA is both a marker and a maker of the diabetic phenotype.